The Relevance of Bourdieusian Theory for a “Sociology of Love” – A Critical Discussion - Nell, Charlotte (Revista Científica Foz, 2020)
The paper starts with the assessment that the Bourdieusian “field approach” has become a central point of reference for contemporary studies on love. It is argued that the reason for this lies within the contribution of Bourdieu’s theory that is able to transcend central theoretical and methodological problems that the phenomenon of love poses to conventional social theory, namely of the status and function of romantic love for late-modern societies. Specifically, Bourdieu’s concepts of symbolic system– habitus, forms of capital and his theory of practice– correspond to problems of conventional social theory in conceptualizing love. Since Bourdieu, however, did not provide a systematic study of love himself, the paper offers a reconstruction of his theory and extrapolates it to the phenomenon of love. The paper proceeds to systemize contemporary Bourdieusian approaches to love. Ultimately, it shows that while Bourdieu’s theory provides a useful lens for studying love as a site of social distinction, it also turns a blind eye to love as a source of intersubjective understanding as well as post-religious transcendence. Accordingly, the paper argues that Bourdieusian theory presents an analytical toolkit rather than a conclusive theory for studying love.